Interaction of a two-layered half-cylindrical shell with acoustic medium - ŠIMKOVÁ, Olga (Archives of Acoustics, 1987)
Some numerical results of investigations into the coupling between the acoustic field inside a two-layered half-cylindrical shell and the vibrations of the containing structure are presented in this paper. An analytical approach has been used to find resonant frequencies of the system as a whole.